Analysis of Buying, Selling, and Leasing Virtual Land in the Metaverse: A Perspective from Sharia Economic Law - Nurjaman, Muhamad Izazi; Al-Hakim, Sofian; Setiawan, Iwan; Sahid, Mualimin Mochammad (Universitas Islam Sultan Agung, 2022)
This research aims to analyze the position of virtual land buying, selling, and leasing practices using cryptocurrency in the metaverse from the perspective of Islamic economic law. This study uses a descriptive analysis method with a normative juridical approach and data analysis techniques through three stages of analysis: focusing the data, presenting the data, and drawing conclusions. The research found that the practice of buying, selling, and leasing virtual land in the metaverse is permissible because it meets the conditions and pillars of a valid contract. The transactions carried out involve intangible assets, namely virtual land and cryptocurrency. In these transactions, there is an expansion of the object of the ijarah (lease) contract, which typically involves the benefit of tangible objects or assets but can also include the benefit of intangible objects or assets, provided that the intangible asset requires another object (a tangible object) or a process that enables the asset to have utility, thus fulfilling the purpose of the contract in accordance with the principles of muamalah maliyyah (financial transactions). The development of the object of the ijarah contract is a scientific contribution to the development of Islamic economic law theory. Therefore, further research is needed on the status of intangible assets as objects of contracts to explore their benefits and legal status in accordance with Sharia principles.